Juridical Analysis of Copyright Ownership of Images Produced by Artificial Intelligence Under Law Number 28 of 2014 on Copyright - Asyrafil Mahdi; Febri Handayani; Nabil Naufal; Agustra Randa; Dany Pratama Putra; Leano Seven (SEAN Institute, 2026)
Artwork in the form of images is a type of creation that receives legal protection as regulated under Article 40 of Law Number 28 of 2014 on Copyright. However, the advancement of Artificial Intelligence (AI) technology capable of producing images based on user prompts raises new issues regarding the recognition of copyright ownership over works produced by AI systems. This research aims to analyze whether images produced through Artificial Intelligence can be recognized as objects of copyright protection under the Copyright Law, as well as to examine the extent of user ownership over images produced by AI. Furthermore, to prevent future legal uncertainty, this research will also discuss the urgency for the Indonesian government, through the Directorate General of Intellectual Property (DJKI), to amend the Copyright Law so that it can better adapt to the developments of AI.